Gli strumenti della cooperazione in rete: Dal catalogo elettronico ai sistemi della ricerca interdisciplinare Internet based cooperation tools: From the OPAC to cross-domain search systems - Paul Gabriele Weston (Saperi storici e nuove tecnologie, 2003)
Such terms as "metadata", "web strategies", "interoperability" are commonly used whenever the perspectives of cultural heritage memories on the web are investigated. The risk that well-established methods of preserving and publishing the output of intellectual and artistic activities could hinder data exchange procedures as well as making the creation of multidisciplinary discovery systems required for carrying out reasearch - even in the humanities - is under assessment. The earliest projects adopted the same electronic format and cataloguing rules shared among classes of items of quite a different nature. Far from being the ideal solution, it has fuelled an animated world-wide debate. Nonetheless, thanks to this strategy North American institutions have created in just over a decade those massive digital archives which are the backbone of American Memory. In the meanwhile research on interoperability was carried out with the purpose of creating cross-domain linking devices and more powerful search tools. The latter should be the basis of networks aimed at fittingly supporting reaserch in the fields of historical and bibliographic studies.